Sick on the job? Myths and realities about mental health and work (Paris, 2012)
"The costs of mental ill-health for the individuals concerned, employers and society at large are enormous. Mental illness is responsible for a very significant loss of potential labour supply, high rates of unemployment, and a high incidence of sickness absence and reduced productivity at work. In particular, mental illness causes too many young people to leave the labour market, or never really enter it, through early moves onto disability benefit. Today, between one-third and one-half of all new disability benefit claims are for reasons of mental ill-health, and among young adults that proportion goes up to over 70%. Indeed, mental ill-health is becoming a key issue for the well-functioning of OECD’s labour markets and social policies and requires a stronger focus on policies addressing mental health and work issues. Despite the very high costs to the individuals and the economy, there is only little awareness about the connection between mental health and work, and the drivers behind the labour market outcomes and the level of inactivity of people with mental ill-health. Understanding these drivers is critical for the development of more effective policies. This report aims to identify the knowledge gaps and begin to narrow them by reviewing evidence on the main challenges and barriers to better integrating people with mental illness in the world of work. "